Metacognitive and creative thinking skills: A post-covid-19 correlational study - Linda Tri Antika; Sukron Sukron; Moch Haikal; Akhmad Fathir (STKIP Persada Khatulistiwa Sintang, 2022)
The facts of learning in education showed that students were less encouraged to develop metacognitive skills and creative thinking skills, so that students were not active and students were less likely to participate in the learning process. This study aimed to determine the correlation of metacognitive skills with creative thinking skills of class XI students in biology subjects. The subjects of this study were students of class XI A IPA at MA Miftahul Ulum Nagasari Congkop in the second semester of academic year 2021/2022, totaling 24 students. This research is quantitative research with regression correlation analysis technique using SPSS Version 26.0. Collecting data on metacognitive skills and creative thinking skills using a rubric that was integrated with an essay test. The results of this study indicated that there was a significant relationship between metacognitive skills and creative thinking skills. Results of the regression analysis showed a large R value of 0.616 which indicated that there was a strong relationship between metacognitive skills and creative thinking skills. The guided inquiry model is the recommended model in empowering metacognitive and creative thinking skills, especially in learning biology.